The development and introduction of production technology and heat treatment of seamless hot-rolled tubes from cr-mo steel grades - S. N. Аudeev; A. V. Strelchanko; V. V. Ivashko (Литьë и металлургия)
In laboratory conditions with further approbation in industrial conditions of OJSC «BSW» – the management Company of Holding «BMC» the optimum modes of heat treatment which allowed to receive the full complex of physical and mechanical properties of seamless pipes from steel of 30khma of group of durability P, M and L demanded by the customer for the further production of the borehole perforators applied in the oil and gas industry were mastered.